Case report: Immunotherapy in rare high TMB pancreatic acinar carcinoma - Wu, Guifu; Fang, Yuting; Bi, Deying; Yang, Wenwei; Sun, Yongkun (Frontiers in Oncology, 2024)
This case report details a patient with Pancreatic Acinar Cell Carcinoma (PACC), a rare malignancy with distinctive biological and imaging features. In the absence of standardized treatment protocols for PACC, we embarked on a diagnostic journey that led to the adoption of an innovative therapeutic regimen in our institution. A 45-year-old female patient presented with a pancreatic mass, which was histologically confirmed as PACC following a biopsy. Subsequent genomic profiling revealed a high tumor mutational burden (21.4/Mb), prompting the initiation of combined immunotherapy and targeted therapy. Notably, the patient experienced a unique adverse reaction to the immunotherapy—recurrent subcutaneous soft tissue nodules, particularly in the gluteal and lower limb regions, accompanied by pain, yet resolving spontaneously. Following six cycles of the dual therapy, radiological evaluations indicated a decrease in tumor size, leading to a successful surgical excision. Over a 20-month post-surgical follow-up, the patient showed no signs of disease recurrence. This narrative adds to the existing knowledge on PACC and highlights the potential efficacy of immunotherapy in managing this challenging condition, emphasizing the importance of close monitoring for any adverse reactions.